Development of a speed protector to optimize user experience in 3D virtual environments. Issue 147 (March 2021) - Wang, Yuyang; Chardonnet, Jean-Rémy; Merienne, Frédéric
Highlights: A minimum-jerk speed profile is applied to virtual locomotion. The embedded speed protector helps reducing cybersickness while maintaining the same mental workload level. Not only acceleration, but also jerk affect user experience during locomotion. Abstract: Virtual walking in virtual environments (VEs) requires locomotion interfaces, especially when the available physical environment is smaller than the virtual space due to virtual reality facilities limitations; many navigation approaches have been proposed according to different input conditions, target selection and speed selection. With current technologies, the virtual locomotion speed for most VR systems relies primarily on rate-control devices (e.g., joystick). The user has to manage manual adaptation of the speed, based on the size of the VE and personal preferences. However, this method cannot provide optimal speeds for locomotion as the user tends to change the speed involuntarily due to non-desired issues including collisions or simulator sickness; in this case, the user may have to adjust the speed frequently and unsmoothly, worsening the situation. Therefore, we designed a motion protector that can be embedded into the locomotion system to provide optimal speed profiles. The optimization process aims at minimizing the total jerk when the user translates from an initial position to a target, which is a common rule of the human motion model. In addition to minimization, we put constraints on speed, acceleration and jerk so that they do not exceed specific thresholds. The speed protector is formulated mathematically and solved analytically in order to provide a smooth navigation experience with a minimum jerk of trajectory. The assessment of the speed protector was conducted in a user study measuring user experience with a simulator sickness questionnaire, event-related skin conductance responses (ER-SCR), and a NASA-TLX questionnaire, showing that the designed speed protector can provide more natural and comfortable user experience with appropriate acceleration and jerk as it avoids abrupt speed profiles.